Undergraduate Biotechnology Students' Views of Science Communication - Edmonston, J.; Dawson, Vaille; Schibeci, R. (Routledge, 2010)
Despite rapid growth of the biotechnology industry worldwide, a number of public concerns about the application of biotechnology and its regulation remain. In response to these concerns, greater emphasis has been placed on promoting biotechnologists’ public engagement. As tertiary science degree programmes form the foundation of the biotechnology sector by providing a pipeline of university graduates entering into the profession, it has been proposed that formal science communication training be introduced at this early stage of career development. The aim of the present study was to examine the views of biotechnology students towards science communication and science communication training. Using an Australian biotechnology degree programme as a case study, 69 undergraduates from all three years of the programme were administered a questionnaire that asked them to rank the importance of 12 components of a biotechnology curriculum, including two science communication items.The results were compared to the responses of 274 students enrolled in other science programmes. Additional questions were provided to the second year biotechnology undergraduates and semi‐structured interviews were undertaken with 13 of these students to further examine their views of this area. The results of this study suggest that the biotechnology students surveyed do not value communication with non‐scientists nor science communication training. The implications of these findings for the reform of undergraduate biotechnology courses yet to integrate science communication training into their science curriculum are discussed.